IntrinsicLiNbO3point defects from hybrid density functional calculations - Li, Yanlu; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Temperature dependent LiNbO3(0001): Surface reconstruction and surface charge - Sanna, S.; Hölscher, R.; Schmidt, Wolf Gero (Applied Surface Science)

Unraveling theLiNbO3X-cut surface by atomic force microscopy and density functional theory - Sanna, S.; Schmidt, Wolf Gero; Rode, S.; Klassen, S.; Kühnle, A. (Physical Review B)

Power model design for ICT systems – A generic approach - Beister, Frederic; Dräxler, Martin; Aelken, Jörg; Karl, Holger (Computer Communications)

Design of an Electrical Interferometer at 120 GHz for Contactless Permittivity Characterization - Wessel, Jan; Schmalz, Klaus; Cahill, Brian; Scheytt, Christoph (Elektrotechnisches Kolloquium)

Architectural Low-Power Design Using Transaction-Based System Modeling and Simulation - Mischkalla, Fabian; Müller, Wolfgang (Embedded Computer Systems: Architectures, Modeling, and Simulation (SAMOS XIV))
Energy efficiency drives the development of more and more complex low-power designs. Based on dynamic power management techniques, multiple voltage islands as well as a huge amount of power states are specified that have to be tested carefully. In this context, low-power design should start at an early stage using state-of-the-art system-level modeling and simulation techniques. However, there is neither a programming language nor any modeling standard that reflects variable power together with its functional side effects in a well-suited abstract manner. To overcome this limitation, we present a modeling approach on top of SystemC TLM to capture low-power design characteristics at electronic system-level. We demonstrate the usability by means of an existing open-source low-power design. The experimental results show that appropriate TLM instrumentation cause only minimal simulation overhead, but offer sufficient details to identify common low-power design errors.

Switchable slow wave transmission line in 130 nm SiGe technology at 115 GHz for phase detection based biosensors - Wessel, Jan; Schmalz, Klaus; Scheytt, Christoph; Meliani, Chafik (Microwave Symposium (IMS), 2014 IEEE MTT-S International)
A 115 GHz slow wave transmission line intended for phase detection based integrated biosensors is presented. The structure was fabricated in a 130 nm SiGe process. It achieved the targeted overall phase shift of 1° at 115 GHz. Moreover, the phase can be adjusted by 16 switches using Heterojunction Bipolar (HBT) transistors leading to a phase resolution of 0.125°. The change in input and output matching over all configurations of the switches is not higher than 0.8 dB and the transmission S 21 varies with less than 0.7 dB. To the authors knowledge, it is the first switchable slow wave structure using microstrip transmission lines along with a bipolar switch circuitry. Moreover, the presented structure provides a very powerful solution for real-time digital read-outs in integrated biosensors, without need of additional signal processing steps.

A 7 GHz biosensor for permittivity change with enhanced sensitivity through phase compensation - Wessel, Jan; Schmalz, Klaus; Scheytt, Christoph; Meliani, Chafik; Cahill, Brian (European Microwave Conference (EuMC))
A calibration technique as well as measurement results for a 7 GHz Biosensor are presented. It is shown that the applied sensor structure can be calibrated by adjusting the phase of a sensing element's transmission S21. This is realized by slowing down the wave traveling a microstrip line serving as a reference in the differential sensor structure. The dielectric properties along with certain physical boundaries of an obstacle covering parts of the microstrip line evoke that effect. Measurements with an ethanol serious along with simulation results showed that sensitivity can be increased substantially with this calibration technique. A change of the real part of the sample's permittivity of 48 leads to a 18 MHz frequency shift.

Wireless 100 Gb/s: PHY layer Overview and Challenges in THz freqency band - Kraemer, Rolf; Wolf, Andreas; Scheytt, Christoph; Kallfass, Ingmar; KrishneGowda, Karthik (2014 IEEE 15th Annual IEEE Wireless and Microwave Technology Conference (WAMICON))
There is a continuous increase of bandwidth-demanding services such as ultra HDTV, 3D TV, etc. which will require data rates up to 100-400 Gb/s for short range wireless communication. This paper introduces a novel mixed-mode design where both analog and digital domain design is considered, which helps in the reduction of power consumption. Parallel Sequence Spread Spectrum (PSSS) is used for physical layer (PHY) baseband technology, which considerably alleviates both transmitter and receiver design.

Fast and Open Virtual Platforms for TriCore-based SoCs Using QEMU - Koppelmann, Bastian; Messidat, Bernd; Becker, Markus; Kuznik, Christoph; Müller, Wolfgang; Scheytt, Christoph (Design and Verification Conference (DVCON EUROPE))
In this paper, we present an efficient approach to virtual platform modeling for TriCore-based SoCs by combining fast and open software emulation with IEEE-1666 Standard SystemC simulation. For evaluation we consider Infineon's recently introduced AURIX processor family as a target platform, which utilizes multiple CPU cores operating in lockstep mode, memories, hierarchical buses, and a rich set of peripherals. For SoC prototyping, we integrate the fast and open instruction accurate QEMU software emulator with the TLMu library for SystemC co-verification. This article reports our most recent efforts of the implementation of the TriCore instruction set for QEMU. The experimental results demonstrate the functional correctness and performance of our TriCore implementation.

Verific-MM: Systematized Verification Metrics Generation with UCIS for Improved Automation on Verification Closure - Kuznik, Christoph; Müller, Wolfgang (Design, Automation and Test in Europe DATE, University Booth, Dresden)
Verific-MM is an approach to systematize and accelerate the coverage plan engineering as well as the verification environment’s (functional) metric code generation -- usually a time-consuming and error-prone task -- in particular by (i) improving automation via assisted model-based approaches, utilizing recent industry standards such as UCIS and (ii) a supporting methodology suitable for various target (functional coverage) languages (IEEE-1800 SystemVerilog, IEEE-1647 e, IEEE-1666 SystemC).

System-on-Chip Design für Funkfrequenzen oberhalb von 100 GHz-Herausforderungen und potenzielle Anwendungen - Scheytt, Christoph (Analog 2014,14. Fachtagung der Gesellschaft für Mikroelektronik, Mikrosystemtechnik und Feinwerktechnik des VDE und VDI)

A -Band Four-Element Butler Matrix in 0.13 µm SiGe BiCMOS Technology - Elkhouly, Mohamed; Mao, Yanfei; Meliani, Chafik; Scheytt, Christoph; Ellinger, Frank (IEEE JOURNAL OF SOLID-STATE CIRCUITS)

Safety Evaluation of Automotive Electronics Using Virtual Prototypes: State of the Art and Research Challenges - Oetjens, Jan-Hendrik; Becker, Markus; Kuznik, Christoph; Müller, Wolfgang; Bannow, Nico; Brinkmann, Oliver; Burger, Andreas; Chaari, Moomen; Chakraborty, Samarjit; Drechsler, R.; Ecker, Wolfgang; Grüttner, Kim; et al. (Design Automation Conference (DAC))
Intelligent automotive electronics significantly improved driving safety in the last decades. With the increasing complexity of automotive systems, dependability of the electronic components themselves and of their interaction must be assured to avoid any risk to driving safety due to unexpected failures caused by internal or external faults. Additionally, Virtual Prototypes (VPs) have been accepted in many areas of system development processes in the automotive industry as platforms for SW development, verification, and design space exploration. We believe that VPs will significantly contribute to the analysis of safety conditions for automotive electronics. This paper shows the advantages of such a methodology based on today's industrial needs, presents the current state of the art in this field, and outlines upcoming research challenges that need to be addressed to make this vision a reality.

Logik und Metaphysik - Ficara, Elena (Hegel – 200 Jahre Wissenschaft der Logik. Deutsches Jahrbuch für Philosophie)

Hegel on the Mathematical Infinite - Ficara, Elena (Siegener Beiträge zur Geschichte und Philosophie der Mathematik)

Hegel's Glutty Negation - Ficara, Elena (History and Philosophy of Logic)

Real-time capable methods to determine the magnet temperature of permanent magnet synchronous motors—A review - Wallscheid, Oliver; Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (IECON 2014-40th Annual Conference of the IEEE Industrial Electronics Society)

Determination of rotor temperature for an interior permanent magnet synchronous machine using a precise flux observer - Specht, Andreas; Wallscheid, Oliver; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014-ECCE ASIA))

Testing the relationship between income inequality and life expectancy: A simple correction for the aggregation effect when using aggregated data - Mayrhofer, Thomas; Schmitz, Hendrik (Journal of Population Economics)

Broke, ill, and obese: is there an effect of household debt on health? - Keese, Matthias; Schmitz, Hendrik (Review of Income and Wealth)

Regional variation in the utilisation of ambulatory services in Germany - Kopetsch, Thomas; Schmitz, Hendrik (Health Economics)

Adaptable AC Input Phase Switching for Optimum Utilization of Various Grid Configurations supplying Power Electronic Converters and EV/HEV On Board Chargers - Schafmeister, Frank; Ide, Peter; Richter, Jörg (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

A Soft-Switching Interleaved DC-DC Converter with Integrated Magnetics for High Voltage Battery Charger - Li, Ronggyuan; Njiende, Hugues; Schafmeister, Frank; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Resistorless Precharging of Boost PFCs by Phase Angle Control of Thyristors - Schafmeister, Frank; Hufnagel, Michael; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Autonomously driven railway cabin convoys — Communication, control design and experimentation - Henke, Christian; Trächtler, Ansgar (2013 International Conference on Connected Vehicles and Expo (ICCVE))

Discrete-time design of adaptive current controller for interior permanent magnet synchronous motors (IPMSM) with high magnetic saturation - Peters, Wilhelm; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Monitoring critical temperatures in permanent magnet synchronous motors using low-order thermal models - Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Real-time implementation of an online Model Predictive Control for IPMSM using parallel computing on FPGA - Leuer, Michael; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Efficiency-optimized Model Predictive Torque Control for IPMSM - Leuer, Michael; Ruting, Arne; Böcker, Joachim (2014 IEEE International Energy Conference (ENERGYCON))

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Power profile based selection and operation optimization of parallel-connected power converter combinations - Vogt, T.; Peters, A.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Voltage sequence control based high-current rectifier system - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Duppe, Gregor; Averberg, Andreas; Wallmeier, Peter (2014 IEEE Energy Conversion Congress and Exposition (ECCE))

A completely modular power converter for high-power high-current DC applications - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Das Erkenntnisproblem und die Mathematik. Zum Streit zwischen dem Marburger Neukantianismus und dem Neofriesianismus - Peckhaus, Volker (Wissenschaftsphilosophie im Neukantianismus. Ansätze – Kontroversen – Wirkungen)

Unsinn und Chance eines Fiktionalismus in der Logik - Peckhaus, Volker (Fiktion und Fiktionalismus. Beiträge zu Hans Vaihingers Philosophie des Als Ob)
Rezension: Zeitschrift für philosophische Forschung 69 (2015), 614–615 (Thomas Uebel)

Ernst Schröder on Pasigraphy (Dossier de la logique philosophique à la logique mathématique) - Peckhaus, Volker (Revue d’histoire des sciences)
Rezension: Math. Rev. MR3330648 (L.G. González); Zbl. Math. 1315.01023 (T.-L. Rădulescu)

In memoriam Helmar Frank

Effects of a mass finishing process on parts produced from Ultem 9085 by Fused Deposition Modeling - Fischer, M.; Schöppner, Volker (ANTEC)
Parts produced by Fused Deposition Modeling (FDM) tend to have rough and undulating surfaces with staircase effects on rounded and slanting areas of the part. This is due to the characteristics of the process. In many fields of application, high demands are made on the optical quality of the part. An improvement in the surface quality of FDM parts made of Ultem*9085 can be achieved through post-treatment with a mass finishing process. In this paper, FDM specimens are post-treated in a disk finishing unit. Influences of the mass finishing process are analyzed with regard to the dependence of surface quality on the various process parameters and on the finishing medium, grinding time and grinding speed. The finishing efficiency depends on the finishing media and decreases for lower finishing time. For all media a lower disk velocity results a smaller grinding effect, but there are clearly differences between the finishing media. The paper also discusses effects of the grinding process on the mechanical properties of the parts. Especially small part geometries and parts build in z-direction tend to break during the finishing process.

Mechanical Analysis of Lightweight Constructions manufactured with Fused Deposition Modeling - Bagsik, A.; Josupeit, S.; Schöppner, Volker; Klemp, E. (29th International Conference of the Polymer Processing Society)
Additive production techniques have the advantage of manufacturing parts without needing a forming tool. One of the most used additive manufacturing processes is "Fused Deposition Modeling" (FDM) which allows the production of prototypes and end-use parts. Due to the manufacture layer by layer, also complex part geometries can be created in one working step. Furthermore, lightweight parts with specific inner core structures can be manufactured in order to achieve good weightrelated strength properties. In this paper the mechanical behavior of lightweight parts manufactured with the 3D production system Fortus 400mc from Stratasys and the material Polyetherimide (PEI) with the trade name Ultem*9085 is analyzed. The test specimens were built up with different inner structures and building directions. Therefore, test specimens with known lightweight core geometries (e.g. corrugated and honeycomb cores) were designed. A four-point bending test was conducted to analyze the strength properties as well as the weight-related strength properties. Additionally the influence of the structure width, the structure wall thickness and the top layer thickness was analyzed using a honeycomb structure.

Ermittlung der Rotortemperatur einer Synchronmaschine mit eingebetteten Permanentmagneten für einen automobilen Traktionsantrieb mittels Beobachter basierend auf elektrischen Größen - Specht, A.

Model-Based Development of DC-DC Converters with Wide Operation Range and High Dynamics - Cao, Z.

Modeling Optimization and Control Design for LCC Resonant Converter Applied in Very Low Frequency High Voltage Generator - Hu, M.

Wirkungsgradoptimale Regelung eines elektrischen Fahrantriebes mit variabler Zwischenkreisspannung - Pohlenz, Daniel

Digital Control for Interleaved Boost Power Factor Correction (PFC) Rectifiers - Grote, T.

Modellprädiktive Regelung permanent erregter Synchronmotoren im Antriebsstrang von Automobilen - Leuer, M.

Evaluierung und Anwendung eines Emulators für elektrische Maschinen in der Entwicklung von Elektro- und Hybridfahrzeugen - Uebener, S.

Traktionsantrieb mit linearem geschalteten Reluktanzmotor für ein autonomes Bahnfahrzeug - Schneider, T.

„Tschuschen“ und „Saujuden“. Kultureller Identitätswandel in dem Roman Zwischenstationen von Vladimir Vertlib - Willeke, Stephanie (Studia theodisca XXI)

Forschung und Lehre: Freund oder Feind? - Lück, Sonja (Die Betriebswirtschaft)

Bedarfsgerechte Angebote für mehrsprachige und internationale Studierende am SchreibCenter der TU Darmstadt - Ballweg, Sandra; Arcudi, Antonio; Bernard, Julia; Hertweck, Lisa; Kimmerle, Lea Luise (Mehrsprachige Lehramtsstudierende schreiben. Schreibwerkstätten an deutschen Hochschulen)

Information processing with topologically protected vortex memories in exciton-polariton condensates - Sigurdsson, H.; Egorov, O. A.; Ma, Xuekai; Shelykh, I. A.; Liew, T. C. H. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Biliteratlität - Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Dominante Sprache - Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Lernersprache - Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Sprachliche Identität - Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Sprachlernbewusstheit - Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Pidginisierung - Efing, Christian; Ballweg, Sandra (Sprachdidaktik: Erstsprache, Zweitsprache, Fremdsprache)

Sprachbildung in allen Fächern - Beese, Melanie; Benholz, Claudia; Chlosta, Christoph; Gürsoy, Erkan; Hinrichs, Beatrix; Niederhaus, Constanze; Oleschko, Sven

Verpasste Lerngelegenheit? Eine qualitative Befragung mehrsprachiger Jugendlicher zur Nutzung von Schulbuchtexten und Konsequenzen für die interkulturelle Lehrerbildung - Niederhaus, Constanze (Methoden – Strukturen – Gestaltung: Lerngelegenheiten und Lernen in der „interkulturellen Lehrerbildung“)

Sprachförderung - Niederhaus, Constanze; Günther, Katrin (Leitfaden individuelle Förderung)

Horky, Philip Sidney, "Plato and Pythagoreanism", Oxford University Press: Oxford 2013 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Leibniz, G.W., "The Leibniz–De Volder Correspondence. With Selections from the Correspondence between Leibniz and Johann Bernoulli, translated, edited, and with an introduction by Paul Lodge", Yale University Press: New Haven and London 2013 (The Yale Leibniz) - Peckhaus, Volker (Mathematical Reviews)

Barendregt, Henk, “Foundations of Mathematics from the Perspective of Computer Verification”, in: Mathematics, Computer Science and Logic–A Never Ending Story, Cham: Springer 2013, 1–49 - Peckhaus, Volker (Mathematical Reviews)

Schreiben im Blick. Schriftliche Formen der sprachlichen Tätigkeit aus dialogischer Perspektive - Karsten, Andrea

Writing: Movements of the self - Karsten, Andrea (Theory & Psychology)
This article presents analyses of excerpts from a study on writing conducted in a dialogical perspective. The study’s material was collected by the auto-confrontation method: writers were videotaped during their work and afterwards confronted with their writing activities. Microanalysis of the material attends to how inner dialogues during writing are “refracted” (Voloshinov) in auto-confrontation. Bakhtin’s notion of the chronotope (time-and-space) as the main tool of analysis helps to discern the changing contexts and position constellations utterances are valid for. It thus sheds light on the positioning movements performed by the writing selves through language. The analyses show various utterance movements traversing the chronotopes involved, ranging from refractions of movements between the writers’ inner dialogues and their texts to retrospective imperatives with a developmental potential. This “dialogical volume” of speech activity presenting itself in writing can contribute to our understanding of the interplay of language and the self.
Keywords: auto-confrontation; chronotope; inner dialogue; microanalysis; positioning; writing

Schreiben ist Dialog. Ergebnisse und Implikationen einer Studie zum ,schreibbegleitenden‘ Sprechen - Karsten, Andrea (JoSch – Journal der Schreibberatung)

Hegemoniale Männlichkeit. Herrschergestalten in Fritz Langs Film Die Nibelungen - Somogyi, Peter (Durchkreuzte Helden. Das ‘Nibelungenlied‘ und Fritz Langs Film ‘Die Nibelungen‘ im Licht der Intersektionalitätsforschung (GenderCodes 17))

Michael Prestwich: Ritter. Der ultimative Karriereführer gelesen von Martin Falk - Somogyi, Peter (literaturkritik.de Nr. 2, Februar 2014)

Phycocyanobilin in solution – a solvent triggered molecular switch - Watermann, Tobias; Elgabarty, Hossam; Sebastiani, Daniel (Phys. Chem. Chem. Phys.)
The chromophore phycocyanobilin changes its spectroscopic behaviour upon solvent change. Our calculations trace this effect back to conformational switching, induced by changes in the hydrogen bonding pattern.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Intermediale Lektüre(n). Ein Konzept für Zu- und Übergänge in intermedialen Lehr- und Lernarrangements - Kruse, Iris (Kinder- und Jugendliteratur in Medienkontexten. Adaption – Hybridisierung – Intermedialität - Konvergenz)

Märchenbilder im Medienverbund. Zugänge zu komplexen Märchenbilderbüchern durch intermediale Lernumgebungen - Kruse, Iris (Bilderbuch und literar-ästhetische Bildung - aktuelle Forschungsperspektiven)

...aber das Buch mag ich jetzt auch! Der kleine Ritter Trenk im medienvergleichenden Zugriff von Vor- und Grundschulkindern - Kruse, Iris (Kirsten Boie. Bielefelder Poet in Residence 2013)

Brauchen wir eine Medienverbunddidaktik? Zur Funktion kinderliterarischer Medienverbünde im Literaturunterricht der Primar- und frühen Sekundarstufe - Kruse, Iris (Leseräume – Zeitschrift für Literalität in Schule und Forschung)

Die (Un-)Wirksamkeit der Warnung. Zur Rezeption ökologischer Dystopien - Kruse, Iris (JuLit)

A comprehensive model of wear, friction and contact temperature in radial shaft seals - Frölich, D.; Magyar, Balázs; Sauer, B. (Wear)
Radial shaft seals are used in a variety of applications, where rotating shafts in steady housings have to be sealed. Typical examples are crankshafts, camshafts, differential gear or hydraulic pumps. In the operating state the elastomeric seal ring and the shaft are separated by a lubrication film of just a few micrometers. Due to shear strain and fluid friction the contact area is subject to a higher temperature than the rest of the seal ring. The stiffness of the elastomeric material is intensely influenced by this temperature and thus contact pressure, friction and wear also strongly depend on the contact temperature. In order to simulate the contact behavior of elastomer seal rings it is essential to use a comprehensive approach which takes into consideration the interaction of temperature, friction and wear. Based on this idea a macroscopic simulation model has been developed at the MEGT. It combines a finite element approach for the simulation of contact pressure at different wear states, a semi-analytical approach for the calculation of contact temperature and an empirical approach for the calculation of friction. In this paper the model setup is presented, as well as simulation and experimental results.
Keywords: Radial shaft seal ring; Contact temperature; Wear; Friction torque; Finite element simulation

Bewegungsbaustellen, Bewegungsräume und Bewegungslandschaften - Albers, Timm (Bewegungserziehung in der frühen Kindheit - wissenschaftliche Grundlagen)

Bewegung macht Sinn: Selbstwirksamkeitserleben im Sportunterricht der Primarstufe - Albers, Timm (Fördermagazin Grundschule)

Kooperation von allgemein und sonderpädagogischen Lehrkräften im Unterricht - Albers, Timm
Keywords: s2n; Scan2Net

Integration in Elterninitiativen - Albers, Timm (Inklusion und Chancengleichheit)
Keywords: s2n; Scan2Net

Was bedeutet Vielfalt: - Was bedeutet Inklusion? - Albers, Timm; Weltzien, Dörte (Vielfalt und Inklusion Kindergarten heute Wissen kompakt)

Zur Qualitätsentwicklung inklusiver Einrichtungen - Albers, Timm (Vielfalt und Inklusion Kindergarten heute Wissen kompakt)

Bewegung und Inklusion - Albers, Timm (Bewegungserziehung in der frühen Kindheit - wissenschaftliche Grundlagen)

Inklusion in der Krippe - Albers, Timm; Jungmann, Tanja (nifbe-Themenheft)

Sprache im Alltag: - Eine Antwort auf PISA - Albers, Timm (Bewegte Kindheit)

Kooperation von allgemeinen und sonderpädagogischen Lehrkräften im Unterricht - Albers, Timm (Kroworsch, S. (Hrsg.). Inklusion im Deutschen Schulsystem. Reihe "Sozialhilfe und Sozialpolitik" des Deutschen Vereins für öffentliche und private Fürsorge e.V.)

Den Umgang mit Vielfalt und Inklusion professionell gestalten - Albers, Timm (Vielfalt und Inklusion, Kindergarten heute Wissen kompakt)

Integrativ arbeitende Elterninitiativen - Albers, Timm (Vielfalt und Inklusion Kindergarten heute Wissen kompakt)

Comparison of Hot Spot Investigations under Laboratory and Field Conditions at Photovoltaic Modules - Wendlandt, Stefan; Krause, Melanie; Berendes, Sarah; Hanusch, Matthias; Drobisch, Alexander; Berghold, Juliane; Schoppa, Michael; Grunow, Paul; Krauter, Stefan (Proceedings of the 29th European Photovoltaic Solar Energy Conference and Exhibition, Amsterdam (The Netherlands), September 22-16, 2014)

Jesuitenhochschule und Fürstbistum. Zur Bedeutung der Theodoriana für den Erhalt des Fürstbistums Paderborn - Süßmann, Johannes (Die Academia Theodoriana. Von der Jesuitenuniversität zur Theologischen Fakultät Paderborn 1614–2014)

Bezwingung durch Qualität. Salomon Kleiners Vedutenfolge von Schloß Pommersfelden - Süßmann, Johannes (1711–2011: 300 Schloß Weißenstein ob Pommersfelden. Wissenschaftliches Symposium der Gesellschaft für Fränkische Geschichte am 15. und 16. September 2011)

Staatsmann – Augenzeuge – Analytiker. Erscheinungsformen Friedrichs II. in seinen Geschichtswerken - Süßmann, Johannes (Repräsentation und Selbstinszenierung Friedrichs des Großen)

Bauten und Positionierung der Neipperg im 18. Jahrhundert - Süßmann, Johannes (Neipperg. Ministerialen – Reichsritter – Hocharistokraten)

Der Übergang von der Grundschule zur weiterführenden Schule aus der Perspektive der Schulqualität: ein Übergangsqualitätsmodell - van Ophuysen, Stefanie; Bloh, Bea (Schulqualität und Schulentwicklung)

Book review: Daniela Carpi (ed.) (2011). 'Bioethics and Biolaw through Literature.'Berlin: de Gruyter - Mildorf, Jarmila (Anglistik)

Exploring ‘our pitiful attempts at connection’: Dialogue in Corey Mesler’s Novel 'Talk' - Mildorf, Jarmila (). Imaginary Dialogues in American Literature and Philosophy: Beyond the Mainstream)

Mapping Imaginary Dialogues in America - Kinzel, Till; Mildorf, Jarmila (Imaginary Dialogues in American Literature and Philosophy: Beyond the Mainstream)

Figurenrede im Roman aus kognitionslinguistischer und narratologischer Perspektive am Beispiel von Jean Rhys’ Roman "Good Morning, Midnight" - Mildorf, Jarmila (Germanisch-Romanische Monatsschrift)

Imaginary Dialogues in American Literature and Philosophy: Beyond the Mainstream